2016
DOI: 10.1021/acscatal.6b00770
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Matters: Tuning the Product Distribution of CO2 Electroreduction on Oxide-Derived Cu Foam Catalysts

Abstract: Mesoporous Cu foams formed by a template-assisted electrodeposition process have been identified as CO2 electrocatalysts that are highly selective toward C2 product formation (C2H4 and C2H6) with C2 efficiencies (FEC2) reaching 55%. The partial current of C2 product formation was found to be higher than that of the (parasitic) hydrogen evolution reaction (HER) at any potential studied (−0.4 to −1.0 vs the reversible hydrogen electrode). Moreover, formate production could largely be suppressed at any applied po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
442
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(490 citation statements)
references
References 56 publications
32
442
1
1
Order By: Relevance
“…9,15,16,20,36 All catalysts were tested for 70 min at -0.7, -0. Table S4, summary of C2 product generation for all catalysts; Tables S18-S33, current density and FE for major products; Tables S34-S49, FE for minor products.…”
Section: Overview Of Co2 Reduction Measurementsmentioning
confidence: 99%
“…9,15,16,20,36 All catalysts were tested for 70 min at -0.7, -0. Table S4, summary of C2 product generation for all catalysts; Tables S18-S33, current density and FE for major products; Tables S34-S49, FE for minor products.…”
Section: Overview Of Co2 Reduction Measurementsmentioning
confidence: 99%
“…Because Cu2O is subject to reduction (back to Cu metal) under CO2RR conditions, the improved performance was initially attributed to Cu metal surface morphology (8,16). But a more recent experiment (15) showed that Cu + sites can survive on the Cu surface for the course of CO2RR.…”
mentioning
confidence: 99%
“…6,7 However, the explanation becomes more complicated when dealing with nanostructured copper materials derived from oxidized precursors, which show both higher activity and greatly enhanced selectivity towards multicarbon products. [8][9][10][11][12][13][14][15][16] It has been hypothesized that this could be related for instance to an increase of local pH, [17][18][19] grain boundaries, 20 undercoordinated sites, 21 or residual oxides. [22][23][24] Several groups have shown the existence of sites with higher CO binding energy in oxidederived copper.…”
mentioning
confidence: 99%